Peran Kinerja Lingkungan Memediasi Pengaruh Green Finance Disclosure dan Leverage terhadap Nilai Perusahaan Pada Perusahaan Subsektor Migas di BEI periode 2021–2024 - Hernika Hernika; Rofiqah Wahdah; Yanuar Bachtiar; Dini Rusqianti (LPPM Universitas KH A. Wahab Hasbullah, 2026)
This analysis aims to evaluate the role of environmental performance in mediating green finance disclosure and leverage on company value in the oil and gas sub-sector on the BEI between 2021 and 2024. The study is based on the urgency of sustainability practices in capital-intensive industries with a significant environmental impact. Using quantitative methods and purposive sampling, 11 samples were selected from a total population of 37 companies. The results of the study revealed that green finance does not affect company value, while leverage has a significant impact on company value. Green finance disclosure was found to influence environmental performance, but leverage was not found to influence environmental performance. Environmental performance does not affect company value. Furthermore, environmental performance was unable to mediate the relationship between green finance disclosure and leverage on company value. Data processing using the e-views tool included analysis of the classical assumptions, panel data and mediation regression analysis.